Evaluation of the Cardiac Safety of Long‐Acting Endectocide Moxidectin in a Randomized Concentration‐QT Study. Issue 6 (19th September 2018) - Kinrade, Sally A.; Mason, Jay W.; Sanabria, Carlos R.; Rayner, Craig R.; Bullock, Julie M.; Stanworth, Stephanie H.; Sullivan, Mark T.
Abstract : Potential effects on cardiac repolarization of single doses of moxidectin, a potent long‐acting macrocyclic lactone endectocide, were assessed in a concentration‐QT (c‐QT; exposure‐response) study. This double‐blind, placebo‐controlled, parallel‐group study in healthy male volunteers ( n = 60) randomized subjects to a single oral dose of moxidectin (4 mg, 8 mg, 16 mg, 24 mg, or 36 mg) or matching placebo. Serial plasma samples for pharmacokinetic (PK) analysis and concurrent triplicate electrocardiogram measurements were taken at baseline and 14 prespecified time points over 72 hours, yielding 900 QT interval‐plasma concentration time‐matched pairs. Moxidectin had no statistically significant or clinically relevant impact on QT interval at any dose level. The primary mixed effects model analysis revealed no treatment‐related impact on the Fridericia‐corrected QT interval‐plasma concentration gradient (−0.0077, 90% confidence interval (CI) −0.0255 to +0.0101).